Thermographic method for very high cycle fatigue design in transportation engineering. (May 2015) - Crupi, V; Epasto, G; Guglielmino, E; Risitano, G
With the increasing progress of the technological development in the transport industry, the required fatigue life has increased, so it is very important to determine a safe fatigue strength for 10 9 cycles. Nowadays, the very high cycle fatigue constitutes one of the main fatigue design criteria for applications in transport industry. In this paper, the infrared thermography and an energetic approach were applied to investigate a tool steel in very high cycle fatigue regime. The traditional energetic approach was developed in order to extend it in very high cycle fatigue regime and to predict the S-N curves. The failure mechanism of the investigated steel was evaluated by means of scanning electron and optical microscopies in order to assess if the nature of microstructure and the metallurgical defects, in terms of inclusions and pores, can influence the crack initiation.